Pengaruh Video Edukasi tentang Pubertas terhadap Pengetahuan Remaja di SMP Negeri 06 Satu Atap Sintang Kalimantan Barat - Selvi Reina Sukardi; Zesika Intan Navelia; Chentia Misse Issabella (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Teenagers' lack of knowledge about puberty will have a negative impact both physically and socially on teenagers. Teenagers will feel anxious and afraid when physical changes occur. Data shows that the rate of early marriage in West Kalimantan is 25%. Researchers are interested in conducting research on the effect of educational videos on increasing teenagers' knowledge about puberty. Research Methods: This research design is a pre-experiment with a one group design model. The sample amounted to 61 female students using simple random sampling technique. The research location was at SMP N 06 One Roof Sintang, Sintang Regency. This research instrument uses a knowledge questionnaire with 30 questions. Statistical tests using the wilcoxom. Research Results: The level of knowledge before being done students who have less knowledge 73.8%, students who have sufficient knowledge 24.6% and who have knowledge 1.6%. have good knowledge or 98.4% and 1 student has sufficient knowledge or 1.6%. With a p-value test result of 0.001 <0.05. The mean difference between pretest and posstest knowledge is 36.18, which means that there is an effect of educational videos on adolescents' knowledge about puberty at SMP N 06 One Roof Sintang. Conclusion: There is an influence of educational video media about puberty on adolescents in SMP N 06 One Roof Sintang, Sintang Regency.